HPV16 E6 Promotes the Progression of HPV Infection-Associated Cervical Cancer by Upregulating Glucose-6-Phosphate Dehydrogenase Expression - Chang, Ye-Fei; Yan, Guo-Ji; Liu, Guang-Cai; Hong, Ying; Chen, Hong-Lan; Jiang, Shui; Zhong, Yong; Xiyang, Yan-Bin; Hu, Tao (Frontiers in Oncology, 2021)
Cervical cancer, which is significantly associated with high-risk human papillomavirus (HPV) infection, currently ranks the fourth most common cancer among women worldwide. Previous literature reported that the elevated expression of G6PD was significantly correlated with the occurrence and deterioration of human cervical cancer, especially with the cervical cancer with HPV16 and HPV18 infection. In this study, we verified that G6PD expression has a strong positive correlation with HPV16 E6 levels in cervical cancer tissues and cells. In addition, regulating the expression of HPV16 E6 significantly affected the proliferation, apoptosis, migration, and invasion in the cervical cancer HeLa cells, as well as the transcript and protein levels of G6PD. The luciferase reporter assay and ChIP assay proved that HPV16 E6 stimulated the transcription of G6PD mRNA and subsequently enhanced the expression of G6PD through directly binding to the specific sites in the promoter of G6PD. Our findings reveal that HPV16 E6 is a novel regulatory factor of G6PD. Furthermore, by regulating the expression of G6PD, HPV16 E6 might promote the proliferation and migration potential, and inhibit apoptosis of cervical cancer cells, which ultimately contributed to the progression and metastasis of cervical cancer.